2016
DOI: 10.1186/s13007-016-0146-2
|View full text |Cite
|
Sign up to set email alerts
|

Protocol: a fast, comprehensive and reproducible one-step extraction method for the rapid preparation of polar and semi-polar metabolites, lipids, proteins, starch and cell wall polymers from a single sample

Abstract: BackgroundThe elucidation of complex biological systems requires integration of multiple molecular parameters. Accordingly, high throughput methods like transcriptomics, proteomics, metabolomics and lipidomics have emerged to provide the tools for successful system-wide investigations. Unfortunately, optimized analysis of different compounds requires specific extraction procedures in combination with specific analytical instrumentation. However, the most efficient extraction protocols often only cover a restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
187
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(192 citation statements)
references
References 77 publications
0
187
0
1
Order By: Relevance
“…In the current workflow Chlamydomonas cells were harvested by centrifugation, but the protocol can also be used with any other strategy for the fast and reproducible sample collection (Huege et al ., ; Hemme et al ., ), especially if labile metabolites like sugar phosphates are to be measured (Arrivault et al ., ). The recently updated version of the MTBE method allowed for the simultaneous extraction of chlorophyll, proteins, starch, polar and semi‐polar metabolites, lipids and cell wall components from 25 μg of plant tissue (Salem et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the current workflow Chlamydomonas cells were harvested by centrifugation, but the protocol can also be used with any other strategy for the fast and reproducible sample collection (Huege et al ., ; Hemme et al ., ), especially if labile metabolites like sugar phosphates are to be measured (Arrivault et al ., ). The recently updated version of the MTBE method allowed for the simultaneous extraction of chlorophyll, proteins, starch, polar and semi‐polar metabolites, lipids and cell wall components from 25 μg of plant tissue (Salem et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…A prerequisite for the detailed, systemic analysis of a biological sample is a robust and high‐throughput‐compatible extraction method for multiple cellular components. We used a previously developed plant tissue extraction method (Salem et al ., ) for the extraction of chlorophyll, lipids, metabolites, proteins and starch from a single sample of Chlamydomonas cell cultures (Figure S6). The use of such an extraction method offers several advantages for multiple‐omics data analysis, since it not only minimizes the number of sample aliquots required for broad systems biological analyses but also reduces the variability between the analytical results.…”
Section: Discussionmentioning
confidence: 99%
“…The RMD is calculated in ppm as [(mass defect/measured monoisotopic mass) × 10 6 )]. It can be used to filter compound classes 23 and it should also be useful to remove artifactual signals. Based on all compounds exported from the Dictionary of Natural Products (DNP; available on DVD v.28.2 from CRC Press), we found that 95% of natural products (NP)s had RMD values of 156.5-969.6 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Biphasic sample extraction was adapted from Salem et al . 2016 23 by adding two cycles of 20 seconds at 6 m/sec. in the FastPrep-24™ benchtop homogenizer (MP Biomedicals™, Illkirch, France) in 1 mL M1 (methyl tert-butyl ether/methanol, 3:1, v:v) extraction solution.…”
Section: Methodsmentioning
confidence: 99%
“…Lipids were extracted from a known mass of ground tissue using the chloroform/methanol protocol (Bligh and Dyer, 1959). Protein extracted with 6 M urea, 2 M thiourea buffer (Salem et al, 2016) was quantified using the Bradford assay (Bradford, 1976). The amino acid content of protein hydrolysates (50% w/v trichloroacetic acid, 6 M HCl, 100°C/24 h) (Antoniewicz et al, 2007) was determined by an established GC/EI-TOF-MS protocol (Luedemann et al, 2008;Fernie et al, 2011;Osorio et al, 2011).…”
Section: Fruit Biomass Measurements and Morphology Analysismentioning
confidence: 99%